2017
DOI: 10.1186/s12889-017-4317-5
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity is associated with a higher burden of obesity and risk of dietary inadequacies among mothers in Beirut, Lebanon

Abstract: BackgroundMixed evidence exists with respect to the association between household food insecurity (HFIS) and obesity in low-to-middle income countries (LMICs), particularly among women. This study aimed to measure socioeconomic correlates of HFIS and explores its association with dietary intake and odds of obesity among mothers in Lebanon, a middle-income country undergoing nutrition transition.MethodsA cross-sectional study was conducted among a representative sample of households (n = 378) in Beirut, Lebanon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
54
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 65 publications
14
54
2
Order By: Relevance
“…Women may also "sacrifice" by eating less from certain foods groups, in favor of their children. A recent study by Jomaa et al (2017) showed that, in an effort to ensure that their children are well-fed, Lebanese mothers may consume less animal-based foods such as meats and may thus have an inadequate intake of several micronutrients including iron, zinc and vitamin B12 [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Women may also "sacrifice" by eating less from certain foods groups, in favor of their children. A recent study by Jomaa et al (2017) showed that, in an effort to ensure that their children are well-fed, Lebanese mothers may consume less animal-based foods such as meats and may thus have an inadequate intake of several micronutrients including iron, zinc and vitamin B12 [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from around the world show that food insecurity is associated with having low levels of education, weak social networks, less social capital, low household income, and being unemployed [13,[27][28][29]. In Lebanon, household income and women's education were inversely associated with HFI [11]. In Uruguay and Brazil, household income strongly correlated with food insecurity [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…HFI affects women's and children's diet diversity which in turn shapes their nutritional outcomes [10]. Women and children in foodinsecure households often consume fewer fruits, vegetables, nuts, and protein-rich foods but more refined grains, bread, and sweets; they are therefore at risk for obesity and diabetes [11][12][13]. Malnutrition before and during pregnancy is associated with a range of health problems for the mother and the developing fetus [14].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] The World Health Organization (WHO) and the United Nations General Assembly, among other professional organisations, recently identified food insecurity as an important proximate driver of the prevalence of metabolic risk factors on the causal pathway to diet-sensitive NCDs. 8 This premise is rooted in the hypothesis that exposure to food insecurity results in compensatory behaviours, which often includes less intake of fruit and vegetables, 9 skipping meals, or reducing portion sizes, 10 and overconsumption of low-cost foods that are high in calories yet deficient in nutritional value. 11 Over time, these compensatory behaviours, perceived as buffers against food insecurity, may lead to malnutrition, which, in turn, initiates a cascade of metabolic risk factors that ultimately precipitate diet-sensitive NCDs.…”
Section: Introductionmentioning
confidence: 99%